Characterization of Pure and L-Proline Doped Potassium Nitrate and Sodium Nitrate Crystals - Velumani, Mathivanan; Paul, Prince Makarios; Haris, Muthiah; Senthilkumar, Muthuswamy; Angamuthu, Abiram; Joseph, Chandrasekaran (Trends in Sciences, 2022)
The crystals of pure and L-Proline doped Potassium nitrate and Sodium nitrate were grown in solution by slow evaporation technique using supersaturated solution of the salts. Characterization studies of the crystals have been done to find the impact of the L-Proline on the regular lattice arrangement of the pure crystal. The Powder XRD spectrum reveals that the pure and doped KNO3 crystals belong to orthorhombic structure; and pure and doped NaNO3 are rhombohedral in nature. This is a unit cell with parameters a = b = c; α = β = γ ≠ 90°. There are small changes in the unit cell dimensions but the structure of the pure and doped crystals remain to be orthorhombic in nature. The FTIR spectrum shows the functional group analysis of the samples. The various decomposition process of the crystals with respect to temperature have been carried out in thermal analysis. The dielectric properties exhibit the variation of dielectric constant, and capacitance with frequency at various temperatures for pure and doped crystals. The doped crystals found to have considerable effect on the optical, thermal and dielectric properties. HIGHLIGHTS Effect of dopant L-Proline on the growth of Potassium nitrate and Sodium nitrate crystals by solution growth was carried out for the first time The studies based on dielectric properties and thermal analysis gives a broad understanding about the influence of the dopant on the pure crystals Variation of dielectric constant, resistance, and capacitance with respect to frequency at various temperatures reveals that the dopant L-Proline has a significant effect GRAPHICAL ABSTRACT